Unraveling amyloid formation paths of Parkinson's disease protein α-synuclein triggered by anionic vesicles. (2017) - Kiskis, Juris; Horvath, Istvan; Wittung-Stafshede, Pernilla; Rocha, Sandra
Abstract: Amyloid formation of the synaptic brain protein α -synuclein ( α S) is related to degeneration of dopaminergic neurons in Parkinson's disease patients. α S is thought to function in vesicle transport and fusion and it binds strongly to negatively charged vesicles in vitro . Here we combined circular dichroism, fluorescence and imaging methods in vitro to characterize the interaction of α S with negatively charged vesicles of DOPS (1, 2-dioleoyl- sn- glycero-3-phospho-L-serine, sodium salt) and DOPG (1, 2-dioleoyl- sn- glycero-3-phospho-(1′- rac -glycerol), sodium salt) and the consequences of such interactions on α S amyloid formation. We found that lipid head-group chemistry modulates α S interactions and also affects amyloid fiber formation. During the course of the experiments, we made the unexpected discovery that pre-formed α S oligomers, typically present in a small amount in the α S starting material, acted as templates for linear growth of anomalous amyloid fibers in the presence of vesicles. At the same time, the remaining α S monomers were restricted from vesicle-mediated nucleation of amyloid fibers. Although not a dominant process in bulk experiments, this hidden α S aggregation pathway may be of importance in vivo .